Enzymes in fruit juice and vegetable processing - Fleuri, Luciana Francisco [UNESP]; Delgado, Clarissa Hamaio Okino [UNESP]; Novelli, Paula Kern [UNESP]; Pivetta, Mayara Rodrigues [UNESP]; Do Prado, Débora Zanoni [UNESP]; Simon, Juliana Wagner [UNESP] (Taylor & Francis, 2015)
Fruits are appreciated for their organoleptic and nutritional characteristics as minerals, vitamins, sugars, and other beneficial components (Klavons et al. 1991). Worldwide production of fruit recorded growth from 420 million tons during 1989-1991 to 500 million tons in 1996, 724.5 million tons in 2009 and 728.4 million tons in 2010. The three largest fruit producers in the world are China, India, and Brazil, which contribute with 43.6% of the world’s total production; however, they basically cater to their domestic markets (FAO 2012; IBGE 2012). It is estimated that 25% to 80% of harvested fruit is lost during transportation and storage due to its high perishability; and hence, they require special care in both postharvest storage and processing (Cardoso 2011). In this context, processing of fruits and vegetables has improved with the production of juices, pulps, purees, jelly, dried fruit, sweets, and jams, which allows uninterrupted consumption, waste reduction, and increased consumption of processed products (Kosseva 2009).